A possible effect of methylphenidate on state anxiety: A single dose, placebo controlled, crossover study in a control group. (30th July 2016) - Segev, Aviv; Gvirts, Hila Zahava; Strouse, Kevin; Mayseless, Naama; Gelbard, Hagar; Lewis, Yael Doreen; Barnea, Yael; Feffer, Kfir; Shamay-Tsoory, Simone G.; Bloch, Yuval
Abstract: Methylphenidate affects state-anxiety in ADHD patients. The current study examines the effect of Methylphenidate on state-anxiety in healthy subjects. In a cross-over, randomized, controlled, double-blind study, 36 healthy subjects received either Methylphenidate or placebo. As a group, no change in state-anxiety was detected with Methylphenidate. However, participants reporting higher anxiety levels experienced a significant and specific state-anxiety reduction following Methylphenidate. Moreover, a strong negative correlation was found between the initial-level of anxiety and net-change in state-anxiety. These changes were unrelated to self-perceived attention levels. Our results point to the state-dependent effects of Methylphenidate on anxiety. Highlights: Methylphenidate affects state-anxiety differentially in healthy subjects, unlike ADHD. This effect applies to state-anxiety in healthy subjects with subclinical anxiety. Transient anxiety states should be addressed in the study of methylphenidate effects.